Blood and Oral Fluid Cannabinoid Profiles of Frequent and Occasional Cannabis Smokers. Issue 8 (26th June 2021) - Hoffman, Melissa A; Hubbard, Jacqueline A; Sobolesky, Philip M; Smith, Breland E; Suhandynata, Raymond T; Sanford, Sandra; Sones, Emily G; Ellis, Shannon; Umlauf, Anya; Huestis, Marilyn A; Grelotti, David J; Grant, Igor; et al.
Abstract: Increased prevalence of cannabis consumption and impaired driving are a growing public safety concern. Some states adopted per se driving laws, making it illegal to drive with more than a specified blood concentration of ∆ 9 -tetrahydrocannabinol (THC) in a biological fluid (typically blood). Blood THC concentrations decrease significantly (∼90%) with delays in specimen collection, suggesting the use of alternative matrices, such as oral fluid (OF). We characterized 10 cannabinoids' concentrations, including THC metabolites, in blood and OF from 191 frequent and occasional users by liquid chromatography with tandem mass spectrometry for up to 6 h after ad libitum smoking. Subjects self-titrated when smoking placebo, 5.9 or 13.4% THC cannabis. Higher maximum blood THC concentrations (Cmax) were observed in individuals who received the 5.9% THC versus the 13.4% THC plant material. In blood, the Cmax of multiple analytes, including THC and its metabolites, were increased in frequent compared to occasional users, whereas there were no significant differences in OF Cmax. Blood THC remained detectable (≥5 ng/mL) at the final sample collection for 14% of individuals who smoked either the 5.9 or 13.4% THC cigarette, whereas 54% had detectable THC in OF when applying the same cutoff. Occasional and frequent cannabis users' profiles were compared, THC was detectable for significantly longer duration in blood and OF from frequent users. Detection rates between frequent and occasional users at multiple per se cutoffs showed larger differences in blood versus OF. Understanding cannabinoid profiles of frequent and occasional users and the subsequent impact on detectability with current drug per se driving limits is important to support forensic interpretations and the development of scientifically supported driving under the influence of cannabis laws.